A novel local audio fingerprinting algorithm - Malekesmaeili, Mani; Ward, Rabab K. (2012 IEEE 14th International Workshop on Multimedia Signal Processing, 2012)
A local fingerprinting algorithm is proposed for the purpose of audio copy detection. The proposed algorithm is robust to noise as well as tempo and pitch modifications of the audio signal. The fingerprints are extracted from adaptively scaled patches of the time-chroma representation of the audio signal. The proposed time-chroma representation, converts tempo change and pitch shift attacks on an audio signal to scaling and circular shift attacks on images, respectively. The proposed algorithm is shown to outperform the state-of-the-art.